Cell Membrane‐Inspired Graphene Nanomesh Membrane for Fast Separation of Oil‐in‐Water Emulsions. (6th May 2022) - Liu, Yanan; Coppens, Marc‐Olivier
Abstract: Graphene exhibits fascinating prospects for preparing high‐performance membranes with fast water transport, due to its low friction with water and extreme thinness. However, for graphene‐assembled membranes, each molecule passing through the membrane should bypass many graphene sheets, which lengthens the molecular pathways and increases the mass transfer resistance. Herein, a graphene nanomesh (GNM) membrane is fabricated that is inspired by cell membranes, including aquaporins with their hydrophilic gate for selective transport and hydrophobic channel for low friction with water, thus resulting in fast water transport, as well as hydrophilic polymer brushes on the membrane surface for fouling resistance. GNM is synthesized by etching nanopores on graphene oxide (GO) nanosheets to significantly shorten the water transport channels, whereas the hydrophobic graphene sheets lead to low water friction; in combination, ultra‐fast, selective water flux is achieved. Also, hydrophilic polymer chitosan is utilized to modify GNM to construct a hydration layer, which suppresses foulants from touching the membrane surface. Accordingly, the permeance of the cell membrane‐inspired graphene nanomesh membrane reaches almost 4000 L m –2 h –1 bar –1, which is about 260 times the permeance in a GO membrane, and the membranes show superior antifouling properties for separating various surfactant‐stabilized oil‐in‐water emulsions. Abstract : Inspired by the structure of cell membranes, including aquaporins for fast water transport and hydrophilic polymers for fouling resistance, a membrane is fabricated by assembling chitosan‐modified graphene nanomesh. This cell membrane‐inspired functionalized graphene nanomesh membrane is endowed with high water‐permeance and superior antifouling when separating surfactant‐stabilized oil‐in‐water emulsions.